Triacylglycerol Profile of a Microalga Chlorococcum Sp. as a Potential Biofuel Feedstock (Journal of Bangladesh Academy of Sciences, 2016)
Chlorococcum sp. has been studied as its possibility for biofuel feedstock. This alga was grown in Zarrouk media. After harvesting, lipid extraction was done by pure n-hexane and mixture of chloroform: methanol (2 : 1)) and hexane: ethanol (3 : 1). Highest oil recovery (21.20%) derived from chloroform: methanol (2 : 1) solvent system from dry biomass whereas the lowest (2.83%) came from n-hexane: ethanol solvent system from wet biomass. GC/MS used for the analysis of extracted lipid revealed that, palmitic acid methyl ester (C17H34O2), 9-octadecenoic acid methyl ester (C19H36O2) were major contents of this biofuel. The acquired fatty acid profile indicates that Chlorococcum sp. could be used as promising biofuel feedstock in near future.Journal of Bangladesh Academy of Sciences, Vol. 40, No. 2, 147-153, 2016